Disorders of acid-base status - P.F. Litvitskiy (Вопросы современной педиатрии)
The second part of the lecture analyzes etiology, key stages of pathogenesis, typical symptoms and principles of treatment of non gas and combined disorders of acid-base balance (ABB). Author characterizes the specificity of some non gas ABB disorders. Control and measure materials for self-control and correction of lecture leaning level are given.Key words: acid-base balance, typical disorders, pathogenesis, principles of elimination.